Resistência ao Fascismo e ao populismo: Da Rua às Redes Sociais, uma Análise das formas de Expressão e Contestação desde os anos 30 até a atualidade. ("Temas Sociais" Journal, 2025)
This article analyzes the evolution of forms of resistance to fascism and populism, from street demonstrations and art in the 1930s to digital activism on social media today. Through bibliographic and documentary research, the study examines the different resistance strategies, comparing the characteristics, potentialities, and challenges of each form of expression and contestation. The analysis reveals that, despite the differences in context and tools, resistance remains a constant struggle in defense of freedom, equality, and social justice. New technologies, especially social media, have profoundly impacted forms of resistance, expanding their reach, facilitating organization, and diversifying forms of expression. However, resistance in the digital age also faces challenges such as disinformation, polarization, and control. The study concludes that resistance to fascism and populism remains a necessary struggle, requiring courage, determination, and the strategic use of all available tools.